Analysis of Harkamtibmas Policy Implementation at the Sector Police Level in Indonesia’s Coastal Border Areas - Said Muhammad Ali Hanafiah; Saputra, Trio (LPPM STIA Lancang Kuning Dumai, 2026)
The maintenance of public security and order (Harkamtibmas) constitutes a core function of the Indonesian National Police, particularly at the sector police (Polsek) level as the frontline of preventive policing. However, the effectiveness of Harkamtibmas implementation faces increasing challenges following the restriction of investigative authority at the sector police level, especially in coastal border areas characterized by geographical vulnerability and transnational crime risks. This study aims to analyze the implementation of the Harkamtibmas policy at the Bantan Sector Police, Bengkalis Regency, by examining the factors that shape its effectiveness and identifying the institutional constraints encountered in practice. Employing a qualitative research design with a case study approach, data were collected through in-depth interviews, field observations, and document analysis, and analyzed using Edwards III’s policy implementation framework, which emphasizes communication, resources, implementer disposition, and bureaucratic structure. The findings reveal that communication and community engagement—particularly through the role of Bhabinkamtibmas—have contributed positively to preventive security efforts and early detection of disturbances. However, limited resources, territorial challenges, and restricted investigative authority significantly hinder response capacity and coordination, thereby affecting public trust and perceived legal certainty. Despite these constraints, the commitment and professionalism of implementers remain strong, enabling partial mitigation of structural limitations. This study contributes to policy implementation and security governance literature by demonstrating how authority restriction operates as a critical structural variable influencing preventive policing effectiveness in decentralized and high-risk contexts. The findings underscore the need for proportional resource allocation, adaptive authority arrangements, and strengthened coordination mechanisms to enhance Harkamtibmas implementation at the local level